Ragam Hias Batik Berbasis Budaya Lokal Transformasi Motif Ukiran Minangkabau Pada Galeri Alam Takambang - Shaheed Fikar; Agusti Efi; Budiwirman Budiwirman (Jurusan Seni Rupa, Fakultas Bahasa dan Seni, Universitas Negeri Padang, 2018)
Batik is one of cultural heritages of Indonesia which has been approved by UNESCO on September 30th 2009. Batik is not only art from Javanese, but it has also developed and become art of West Sumatra people. Batik in West Sumatra is known with batik from clay. Batik from Minang has uniqueness of motive, color, character and color identity and typical of complexion. Therefore, the research aimed to describe about batik art in Minang in Alam takabang gallery. This research was qualitative research using descriptive method. This research focused on:) what is form of Gadang House carving motive design in Alam takambang gallery, 2) analyzing designing process and 3) making batik in Alam Takambang Gallery. Data collecting was analyzed using qualitative analysis. The result of the research showed that motive form of batik fabric in Alam Takambang began from carving typical motive of Minangkabau. In design analysis, it was found transformation and process and it had unique change because motive in wood was made in batik fabric in new creative motive in realizing material culture from Minangkabau. Batik business in Alam Takambang Gallery used canting technique (Tulis Batik) and stamp technique in making Batik. Alam Takambang Gallery as one of businesses to introduce tradition of Batik with typical motive of West Sumatra.